Cytosolic and Mitochondrial Malic Enzyme Isoforms Differentially Control Insulin Secretion - Pongratz, Rebecca L.; Kibbey, Richard G.; Shulman, Gerald I.; Cline, Gary W. (The Journal of biological chemistry, 2007)
In islet β-cells and INS-1 cells both the high activity of malic enzyme and the correlation of insulin secretion rates with pyruvate carboxylase (PC) flux suggest that a pyruvate-malate cycle is functionally relevant to insulin secretion. Expression of the malic enzyme isoforms in INS-1 cells and rat islets was measured, and small interfering RNA was used to selectively reduce isoform mRNA expression in INS-1 cells to evaluate its impact on insulin secretion. The cytosolic NADP+-specific isoform (ME1) was the most abundant, with the mitochondrial isoforms NAD+-preferred (ME2) expressed at ∼50%, and the NADP+-specific (ME3) at ∼10% compared with ME1. Selective reduction (89 ± 2%) of cytosolic ME1 mRNA expression and enzyme activity significantly reduced glucose (15 mm:41 ± 6%, p < 0.01) and amino acid (4 mm glutamine ± 10 mm leucine: 39 ± 6%, p < 0.01)-stimulated insulin secretion. Selective small interfering RNA reduction (51 ± 6%) of mitochondrial ME2 mRNA expression did not impact glucose-induced insulin secretion, but decreased amino acid-stimulated insulin secretion by 25 ± 4% (p < 0.01). Modeling of the metabolism of [U-13C]glucose by its isotopic distribution in glutamate indicates a second pool of pyruvate distinct from glycolytically derived pyruvate in INS-1 cells. ME1 knockdown decreased flux of both pools of pyruvate through PC. In contrast, ME2 knockdown affected only PC flux of the pyruvate derived from glutamate metabolism. These results suggest a physiological basis for two metabolically and functionally distinct pyruvate cycles. The cycling of pyruvate by ME1 generates cytosolic NADPH, whereas mitochondrial ME2 responds to elevated amino acids and serves to supply sufficient pyruvate for increased Krebs cycle flux when glucose is limiting.